Development of a Home-Based Nursing Intervention Model for Patients With Heart Failure: A Qualitative Feasibility Study - Motohiro Sano PhD, RN; Tomoko Majima PhD, RN (SAGE Publishing, 2021)
Aim: To develop and verify the feasibility of a personalized home-based heart failure (HF) nursing intervention model to support HF patients, promote self-management, and avoid HF exacerbation and re-hospitalization. Methods: Based on processes established in previous studies, literature reviews, and evidence-based guidelines and theories, we developed the nursing intervention model for patients with HF. The goal of this model is to harmonize symptom deterioration prevention behavior and individual lifestyle. After intervention, we conducted semi-structured interviews with participants, and data were transcribed verbatim, after which qualitative content analysis was employed. The contents of visiting nursing practice, opinions on this nursing model, and self-management in patients with HF were analyzed qualitatively and inductively from the viewpoint of practicality and acceptability. Results: Five nurses who provided interventions, as well as five patients with HF, participated in this study. Accordingly, our findings showed that the framework, assessment, and nursing intervention contents of this model can be practical for everyday home nursing visitations. Conclusions: The content has been revised so that more visiting nurses can use them, including those who have less cardiovascular nursing experience.